2022
DOI: 10.1039/d2dt00279e
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of CO2 catalyzed by heteroscorpionate zwitterionic zinc and magnesium hydride complexes

Abstract: Heteroscorpionate zinc hydride complex LZnH 2, (L= (MePz)2CP(Ph)2NPh, MePz = 3,5-dimethylpyrazolyl), its formate complex 3 and magnesium hydride complex LMgH 5 with same ligand were synthesized and detected for the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…6−14 Further studies based on a variety of transitionmetal catalysts such as Ir, 15 Pd, 16,17 Ru, 18−21 Mn, 22−24 Fe, 25−30 Co, 31 Ni, 11,12,32−34 and Cu, 35−37 have indicated that reduction of CO 2 with E−H can provide diverse reduced monocarbon (C1) chemicals. 38,39 In addition to methoxy, 11,15,19,22,23,32,34,40 these reactions can also produce reduced formoxy 20,35,36,41−43 and acetyl compounds, 26,28,33 and these C1 derivatives are valuable synthons for the construction of new C−C, C−N, C− O, C−P, and C−S bonds. 26,28,33 In this context, controlling the reaction selectivity to harvest the desired C1 product is essential for the incorporation of CO 2 into the subsequent reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6−14 Further studies based on a variety of transitionmetal catalysts such as Ir, 15 Pd, 16,17 Ru, 18−21 Mn, 22−24 Fe, 25−30 Co, 31 Ni, 11,12,32−34 and Cu, 35−37 have indicated that reduction of CO 2 with E−H can provide diverse reduced monocarbon (C1) chemicals. 38,39 In addition to methoxy, 11,15,19,22,23,32,34,40 these reactions can also produce reduced formoxy 20,35,36,41−43 and acetyl compounds, 26,28,33 and these C1 derivatives are valuable synthons for the construction of new C−C, C−N, C− O, C−P, and C−S bonds. 26,28,33 In this context, controlling the reaction selectivity to harvest the desired C1 product is essential for the incorporation of CO 2 into the subsequent reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) is a sustainable carbon source in building biomass, fossil fuels, and organic chemicals . The long-standing interest in the utilization of CO 2 for chemical synthesis has provoked research on inexpensive metal catalysts which can process CO 2 . Prior studies have shown that hydroboranes and hydrosilanes (E–H, E = B or Si) are suitable reducing agents for transforming CO 2 under mild reaction conditions. Further studies based on a variety of transition-metal catalysts such as Ir, Pd, , Ru, Mn, Fe, Co, Ni, ,, and Cu, have indicated that reduction of CO 2 with E–H can provide diverse reduced monocarbon (C1) chemicals. , In addition to methoxy, ,,,,,,, these reactions can also produce reduced formoxy ,,, and acetyl compounds, ,, and these C1 derivatives are valuable synthons for the construction of new C–C, C–N, C–O, C–P, and C–S bonds. ,, In this context, controlling the reaction selectivity to harvest the desired C1 product is essential for the incorporation of CO 2 into the subsequent reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…In these hydroboration processes, the catalyst plays the role of enhancing the hydricity of the B–H moiety, increasing the electrophilicity of the carbonyl groups, and/or providing a hydride shuttle from boron to CO 2 as well as the transient products. To date, a plethora of molecular catalysts have been developed to promote the reduction of CO 2 with boranes, ranging from Lewis bases (amines, phosphines, and carbon-based nucleophiles) and frustrated Lewis pairs , to main-group hydrides ([B]–H, ,− , [Al]–H, , [Ga]–H, [Ge]–H, and [Sn]–H) and metal complexes (containing Mo, Mn, Fe, , Ru, , Co, , Ir, Ni, , Pd, ,, Cu, , or Zn).…”
Section: Introductionmentioning
confidence: 99%
“…3 a By using this NiH active species, the catalytic cycle for the reduction of CO 2 toward the methanol equivalent (MeOBcat) could be well established, with a desirable turnover frequency (TOF, 495 h −1 ). Following this pioneering work, a wide scope of transition metal-based catalysts, 3 organocatalysts 4 and frustrated Lewis pairs (FLPs 5 ) have been developed in succession for the catalytic hydroboration of CO 2 with various kinds of organoboranes, including HBpin, HBcat, 9-borabicyclo[3.3.1]nonane{H(9-BBN) 2 } and BH 3 ·SMe 3 . Among these examples, it is noteworthy that a few of tailor-made main group metal hydride compounds with polarized M–H bonds exhibit transition metal-like reactivity in mediating the hydroboration of CO 2 with hydroboranes.…”
Section: Introductionmentioning
confidence: 99%